Pelaksanaan Asas Ketertiban Umum dalam Penetapan Arbitrease Internasional di Indonesia Studi Kasus: Putusan Mahkamah Agung Nomor 67 PK/Pdt.Sus-Arbt/2016 - Muhamad Guntar Hariyudi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This research aims to understand the causes of the difficulty in implementing the execution of international arbitration awards in Indonesia. Meanwhile, the State of Indonesia has recognized foreign arbitration decisions through Supreme Court Regulation No.1 of 1990. The research method used is a normative juridical approach using two sources of law, namely primary and secondary sources of law. Primary sources of law refer to the Supreme Court Decision Number 67 PK / Pdt.Sus-Arbt/2016 and PERMA Number 1 of 1990. Secondary sources of law refer to Cut Memi's book entitled International Commercial Arbitration Application of Clauses in District Court Decisions. The research results show that the Supreme Court's decision has rejected the implementation of international arbitration decisions because it is considered to have intervened in the legal system in Indonesia and has violated public order.Keywords: International Arbitration, Public Order Principles, Execution